Progression of female leadership representation in disney Princess films through Roland Barthes' semiotic analysis - Jessica Hengkenang; Eka Noviana (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
This study examines the progression of female leadership representation in Disney Princess films through the lens of Roland Barthes’ semiotic theory. The phenomenon addressed is the global circulation of princess narratives and the problem is how repeated visual constructions in children’s media may shape early gender schemas and assumptions about leadership. Using a qualitative content analysis, the study purposively sampled three representative films Snow White and the Seven Dwarfs, Beauty and the Beast, and Frozen selected to reflect Pre-Transition, Transition, and Progression phases of Disney princess narratives. Primary data were drawn from key scenes identified through repeated viewings; visual units (costume, framing, props, gesture, and spatial composition) were coded and analyzed across denotative, connotative, and mythic levels following Barthesian procedures. Findings indicate a clear visual progression: early films privilege domesticity and appearance, transitional films introduce intellectual agency yet maintain social constraints, and contemporary films normalize female authority via symbolic markers of institutional power. The study concludes that Disney’s visual constructions have shifted from naturalizing female passivity toward legitimizing women’s leadership in the public sphere. Implications include the need for media literacy interventions for educators and parents, and recommendations for content creators to design more inclusive visual narratives that support gender-equal leadership models. The research contributes to visual communication and gender studies by demonstrating how semiotic reading of cinematic visuals reveals the gradual normalization of female leadership across historical phases of films.